Fluorescence Polarization Immunoassay for Rapid, Sensitive Detection of the Herbicide 2,4-Dichlorophenoxyacetic Acid in Juice and Water Samples - Liliya I. Mukhametova; Marya K. Kolokolova; Ivan A. Shevchenko; Boris S. Tupertsev; Anatoly V. Zherdev; Chuanlai Xu; Sergei A. Eremin (Biosensors)
2,4-Dichlorophenoxyacetic acid (2,4-D) is one of the popular herbicides that is widely used in agriculture and can be found in food and water. A rapid and sensitive fluorescence polarization immunoassay (FPIA) was proposed for the detection of 2,4-D in juice and water. New tracers, 2,4-D-buthylenediamin fluoresceinthiocarbamyl (2,4-D-BDF) and 2,4-D-glycine aminofluorescein (2,4-D-GAF), were obtained and characterized. Monoclonal antibodies (MAb) obtained against 2,4-D were used as a recognition reagent. The kinetics of the interaction of MAb and tracers were studied, and the kinetic parameters of their binding were calculated. High specificity of binding of tracers and MAb was shown. In this work, an approach was elaborated on to reduce the detection limit of 2,4-D by the FPIA method by changing the volume of the studied sample. The optimized FPIA in a competitive format was characterized by the LODs of 2,4-D 8 and 0.4 ng/mL and the working ranges 30–3000 ng/mL and 3–300 ng/mL for juice and water, respectively. The entire test cycle (from sample receipt to evaluation of the analysis results) took only 20 min. The test for the recovery of 2,4-D in juice and water gave values from 95 to 120%, which demonstrated the reliability of the herbicide determination in real samples.